2022
DOI: 10.1007/s00436-021-07406-2
|View full text |Cite
|
Sign up to set email alerts
|

Cystoisospora belli, liver disease and hypothesis on the life cycle

Abstract: Cystoisospora belli causes chronic diarrhoea, acalculous cholecystitis, cholangiopathy and disseminated cystoisosporosis in patients with AIDS. Clinical manifestations and histological stages during C. belli infection in a patient with AIDS and liver disease were described. It was possible to identify sporozoite-like structures in the villus epithelium of the duodenum, close to the vascularization that underlies the basal membrane and unizoite tissue cysts near to the vascularization in the lamina propria. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As with another coccidian, C. belli has a sexual and asexual life cycle. Humans are the only known host for this parasite, and the infection is acquired through the ingestion of sporulated oocysts through contaminated water and food [5]. After the invasion of the small intestinal epithelium and completes its life cycle within the cytoplasm of the enterocytes, Oocysts (diagnostic stage) are excreted with the faeces and develop outside the host into mature cysts, each with two sporocysts which contain four sporozoites each (infective stage) [6].…”
Section: Introductionmentioning
confidence: 99%
“…As with another coccidian, C. belli has a sexual and asexual life cycle. Humans are the only known host for this parasite, and the infection is acquired through the ingestion of sporulated oocysts through contaminated water and food [5]. After the invasion of the small intestinal epithelium and completes its life cycle within the cytoplasm of the enterocytes, Oocysts (diagnostic stage) are excreted with the faeces and develop outside the host into mature cysts, each with two sporocysts which contain four sporozoites each (infective stage) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies shown that C. belli does not require an intermediate host and it can be transmitted directly from person to person through the ingestion of sporulated oocysts from contaminated water and food [5]. After the invasion of the small intestinal epithelial cells and completes its life cycle within the cytoplasm of the enterocytes, oocysts (diagnostic stage) are excreted with the feces and develop outside the host into mature Journal homepage www.jzs.univsul.edu.iq…”
Section: Introductionmentioning
confidence: 99%